2003
DOI: 10.1037/1528-3542.3.3.254
|View full text |Cite
|
Sign up to set email alerts
|

The appraisal basis of anger: Specificity, necessity and sufficiency of components.

Abstract: The nature of the association between anger and 5 appraisal-action tendency components-goal obstacle, other accountability, unfairness, control, and antagonism-was examined in terms of specificity, necessity, and sufficiency. In 2 studies, participants described recently experienced unpleasant situations in which 1 of the appraisal-action tendency components was present or absent and indicated which emotions they had experienced. The results showed that (a) other accountability and arrogant entitlement, as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 254 publications
(245 citation statements)
references
References 48 publications
9
232
3
1
Order By: Relevance
“…Besides its key role in the influential frustration Áaggression hypothesis (Dollard, Doob, Miller, Mowrer, & Sears;1939), it has also been adopted under various forms by numerous more recent appraisal theorists as a major 1 Some appraisal theories also hypothesise that the appraisal of power or control is an important determinant of anger (e.g., Roseman et al, 1990;Scherer, 1993). This appraisal was not included in the present study because empirical evidence so far has failed to show a consistent association between this appraisal and anger (see, e.g., Kuppens, Van Mechelen, Smits, & De Boeck, 2003) and in the present study we wanted to include only those appraisals that have been proven to be predictive for anger. component of anger and anger-like emotions; the latter include frustration (Averill, 1982), perceived goal-obstacle (Ellsworth & Smith, 1988;Smith & Ellsworth, 1985), motivational incongruence (Smith & Lazarus, 1993), motive inconsistency (Roseman et al, 1990), undesirable event (Ortony et al, 1988), goal obstructiveness (Scherer, 1993), and goal blocking (Izard, 1977).…”
Section: Central Appraisals Of Angermentioning
confidence: 96%
See 2 more Smart Citations
“…Besides its key role in the influential frustration Áaggression hypothesis (Dollard, Doob, Miller, Mowrer, & Sears;1939), it has also been adopted under various forms by numerous more recent appraisal theorists as a major 1 Some appraisal theories also hypothesise that the appraisal of power or control is an important determinant of anger (e.g., Roseman et al, 1990;Scherer, 1993). This appraisal was not included in the present study because empirical evidence so far has failed to show a consistent association between this appraisal and anger (see, e.g., Kuppens, Van Mechelen, Smits, & De Boeck, 2003) and in the present study we wanted to include only those appraisals that have been proven to be predictive for anger. component of anger and anger-like emotions; the latter include frustration (Averill, 1982), perceived goal-obstacle (Ellsworth & Smith, 1988;Smith & Ellsworth, 1985), motivational incongruence (Smith & Lazarus, 1993), motive inconsistency (Roseman et al, 1990), undesirable event (Ortony et al, 1988), goal obstructiveness (Scherer, 1993), and goal blocking (Izard, 1977).…”
Section: Central Appraisals Of Angermentioning
confidence: 96%
“…From an empirical point of view, there are several findings that suggest that the relationship between emotional experience and its appraisal components may be less consistent then is generally assumed. For instance, Kuppens, Van Mechelen, Smits, and De Boeck (2003) showed that the anger appraisals of frustration, other accountability, and unfairness do not necessarily accompany the experience of anger and vice versa. Also, findings from other studies suggest that emotions are not always characterised by the same pattern of appraisals (Parkinson, 1999;Reisenzein, 2000).…”
Section: Individual Differences In Appraisal and Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is represented in most, if not all, accounts of anger (for an overview, see Kuppens, Van Mechelen, Smits, & De Boeck, 2003), although it must be noted that the term frustration is sometimes also used to refer to a low-level emotional state itself (e.g., Roseman, Spindel, & Jose, 1990). In either case, frustration is considered a central component of anger (e.g., Averill, 1982;Berkowitz, 1989;Dollard, Doob, Miller, Mowrer, & Sears;1939;Fehr et al, 1999).…”
Section: Frustrationmentioning
confidence: 99%
“…Associated with aggression and selfassertion, anger motivates an assertive response when important goals are threatened (Kuppens, Van Mechelen, Smits, & De Boeck, 2003). Anger is an approach-oriented emotion (Berkowitz & Harmon-Jones, 2004)-when angry, people try to deal with the threat to their goals.…”
Section: Anger and Disgust As Aesthetic Emotionsmentioning
confidence: 99%